The Effect of Film Nostalgia on Visiting Tourist Attractions (Case Study: “What's The Time in Your World?” Film) - Seyed Mojtaba Moussavi Neghabi; Seyed Ali Hosseini; Nima Moshiri Langroudi (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2021)
The development of film and television entertainment has led to the rapid growth of film tourism in recent years (Tang, 2020). People spend a lot of their free time watching movies (Cormby, Sanford & Pickering, 2019: 14). Following the global trend, Iranians also watch more than two hours of their free time on TV every day (Moeidfar, 1399). Besides the beginning of the Corona pandemic and the imposition of severe restrictions on the closure of recreational and sports centres and domestic and international travel (Akbari and Ansari, 1399) have caused part of the leisure time spent travelling and travelling to other things, specially allocated watching Film. According to statistics, after the spread of the Coronavirus in the United States, watching online movies, TV, and online TV has increased by 39, 39 and 38%, respectively (World Wide Web Index, 2020), a factor in the growing importance of Film in tourism marketing.Corona restrictions have reduced international tourism by 78% (Chen, 2020). The OECD estimates this damage at up to 80% (Stacey, 2020). In Iran, the tourism sector has been severely challenged due to the outbreak of coronary heart disease and many accommodations and tourism centres have been closed during this period (Hassanpour, Shahi and Arjangmehr, 1399). Of course, it is expected that with the global injection of the corona vaccine, tourism will gradually return to its place. According to statistics obtained from research in Indonesia, 78% of people will travel again after the end of the corona, and even 65% of these people stated that they travelled within the first 6 months after the end of the corona (Vachioni, 2020). One can expect domestic tourism to grow first and then travel abroad. Therefore, we must use media attractions, especially movies, to attract tourists and compete with other destinations during this period.MethodsThe present study is applied research in terms of purpose, survey research in terms of data collection method, and descriptive research. Data analysis and hypothesis testing were performed by structural equation modelling of least squares (PLS-SEM) using SmartPLS software, version 3.3. The questionnaire was also used to measure variables and collect data. This questionnaire consists of 46 questions, of which 7 items are related to demographic questions, and the rest are designed as follows: Introduction to the destination (5 questions, researcher-made); Filming location nostalgia (4 questions, taken from (Kim et al., 2019)); Film music nostalgia (4 questions, researcher-made); Nostalgia for the story of the Film (6 questions, taken from (Kim et al., 2019)); Nostalgia for movie actors (5 questions; taken from (Kim and Kim, 2018a)); Following the actors (4 questions, (Kim and Kim, 2018a)); Creating and maintaining a tourist attraction (4 questions, made by a researcher); Music tourism (3 questions, researcher-made) and travel motivation (4 questions, taken from (Oha and Kim, 2020)). The validity and reliability of the questionnaire were evaluated and confirmed based on composite reliability, representative reliability, convergent validity and differential validity.The statistical population of the present study is all people who have watched the movie "What time is it in your world" at least once? In other words, the condition for completing the questionnaire is to watch this Film. Respondents were asked to watch the video before completing the questionnaire, and one of the questionnaire questions was about the number of times the respondent had watched the video. The questionnaire was designed online, and its link is available to people. Using G * Power software, considering the effect size (f2) equal to 0.15, the significance level of 5%, the statistical power of 80%, and 5 predictor variables, the minimum sample size of 132 items was determined. After several follow-up sessions, 164 questionnaires were collected, of which 4 were excluded from the analysis because the number of missing data was more than 15%, and 160 questionnaires were used in the analysis.Discussion and ResultsThe present study is applied research in terms of purpose, survey research in terms of data collection method, and descriptive research. Data analysis and hypothesis testing were performed by structural equation modelling of least squares (PLS-SEM) using SmartPLS software, version 3.3. The questionnaire was also used to measure variables and collect data. This questionnaire consists of 46 questions, of which 7 items are related to demographic questions, and the rest are designed as follows: Introduction to the destination (5 questions, researcher-made); Filming location nostalgia (4 questions, taken from (Kim et al., 2019)); Film music nostalgia (4 questions, researcher-made); Nostalgia for the story of the Film (6 questions, taken from (Kim et al., 2019)); Nostalgia for movie actors (5 questions; taken from (Kim and Kim, 2018a)); Following the actors (4 questions, (Kim and Kim, 2018a)); Creating and maintaining a tourist attraction (4 questions, made by a researcher); Music tourism (3 questions, researcher-made) and travel motivation (4 questions, taken from (Oha and Kim, 2020)). The validity and reliability of the questionnaire were evaluated and confirmed based on composite reliability, representative reliability, convergent validity and differential validity.In the present study, using the least partial structural equation modelling (PLS-SEM), the conceptual model of the research was tested. Out of 12 paths defined in the model, 11 research hypotheses were confirmed, and only one hypothesis was not accepted at the significance level of 0.95. This study shows that film nostalgia is positively related to travel motivation, which is consistent with previous studies that show that film nostalgia greatly affects tourist attitudes and behaviours (Oha and Kim, 2020; Kim et al., 2017). The effect of total film nostalgia on travel motivation equals 0.727, which shows the high impact of film nostalgia on travel motivation. In particular, the research findings show that among the various dimensions of film nostalgia, most viewers who feel nostalgic for film music and film actors are more motivated to visit the destination. Perhaps the high impact of music nostalgia on travel motivation can be attributed to the harmony of film music with the culture and environment of the destination (Guilan) because the average response to the phrase "film music has the spirit of Guilan." Above average. But, on the contrary, due to the lack of coordination of the Film's story with the destination (Gilan), the effect of the Film's nostalgia on the motivation to travel is low. Therefore, it is suggested to increase the impact of film nostalgia on tourism to coordinate all dimensions of film nostalgia, i.e. music, story, actors and filming location, with the intended destination space.One of the differences between the present study and previous studies is the effect of familiarity with the destination on the nostalgia of the Film, which was accepted at the significance level of 0.000. In other words, the viewer's previous familiarity with the location of the filming, by searching for the tourist attractions of the destination on the Internet or a previous visit, increases the feeling of nostalgia and thus has a greater impact on travel motivation. Another hypothesis confirmed in the present study is the positive effect of film nostalgia on music tourism. The feeling of nostalgia for the film positively impacts the spectator's motivation to attend the film singer's concert or buy a film music album. This research finding is consistent with previous studies (Kim et al., 2019). However, the hypothesis of a direct effect of music tourism on travel variables at the significance level of 0.95 was not accepted. Of course, the indirect effect of film music nostalgia on travel motivation with a total effect of 0.284 is significant. Another aspect of the present study with previous studies is the study of the hypothesis of the impact of film nostalgia on the creation and maintenance of tourist attractions, which was confirmed with a path coefficient of 0.434.